Penerapan Permainan Sentra Persiapan terhadap Perkembangan Kognitif Anak Inklusi di RA Ar- Rafif Sleman Yogyakarta - Fatmawati, Fatmawati (ACIECE, 2019)
This research is motivated by the preparation of learning center learning methods conducted bythe teacher with very interesting. The purpose of this study is to find out how the learningmethods of center games are used by teachers in arousing children's development. This type ofresearch is descriptive with a qualitative approach. The results of research on the play centerpreparation carried out by the teacher are adjusted to the themes and sub-themes, the methodsused by the teacher in the play center preparation can develop children's understanding